Kidney embolization induces prompt organ response in a 86‐year‐old patient with MGRS‐related AL‐amyloidosis. Issue 2 (13th December 2018) - Küchlin, Sebastian; Duffner, Johannes; Scheubeck, Sophia; Schoeller, Katja; Maruschke, Lars; Seidl, Maximilian; Engelhardt, Monika; Walz, Gerd; Prager, Eric Peter; Waldschmidt, Johannes Moritz
Abstract: Despite substantial improvements following the introduction of novel agents and antibodies, amyloid light‐chain (AL)‐amyloidosis still carries a grim prognosis. Here, we report on the case of a severely frail 86‐year‐old patient suffering from monoclonal gammopathy of renal significance (MGRS)‐associated AL‐amyloidosis with a diuretic‐refractory nephrotic syndrome. In this patient, treatment with bortezomib–dexamethasone effectively induced a serological response, but was unfortunately poorly tolerated and failed to promote renal recovery fast enough to prevent secondary complications. Facing ongoing nephrotic syndrome, we performed unilateral kidney embolization and observed a substantial improvement of hypoalbuminemia accompanied by a significant gain in overall quality of life despite the necessity for thrice weekly dialysis. It can be concluded that systemic drugs in MGRS typically do not lead to instantaneous organ recovery but may initially rather be associated with substantial treatment‐related morbidity. In this setting, unilateral renal artery embolization is effective to treat nephrotic syndrome and its secondary complications. The risk of potentially adverse effects, including post‐embolization syndrome, can be minimized by unilateral embolization, still noting that also one‐sided renal ablation has to be balanced against the requirement for life‐long renal replacement therapy. Prospective controlled trials in a more comprehensive cohort will be needed to estimate the overall benefit of kidney embolization relative to novel agent therapies in frail patients with MGRS‐related AL‐amyloidosis.